La ricerca visuale riflessiva tra produzione e ricezione: spunti dall’approccio culturale - Sacchetti, Francesco (SocietàMutamentoPolitica, 2016)
Social sciences have long lingered on the legitimacy of visual search techniques about the production of knowledge. This happens in an academic context where writing has historically a clear supremacy as medium for communication and dissemination of scientific thought. This paper proposes some points for reflection regarding the current debate on the epistemological and methodological view, with particular reference to the cultural and reflexive dimension. After a discussion of some elements of contemporary visual culture and about the dimension of participation, it will be introduced a further element of reflection about the reception of the visual product and the technical possibility of incorporation of multimedia visual content in the press works.